Reading fluency as the bridge between decoding and reading comprehension in Chinese children - Lucy Shih-Ju Hsu; Kevin Chan; Connie Suk-Han Ho (Frontiers in Psychology, 2023)
PurposeReading fluency has been considered an essential component of reading comprehension, but it is yet to be examined in a reading model in a non-alphabetic writing system. This study investigated whether reading fluency could be identified as a separate construct from decoding and examined the unique role of reading fluency in the Simple View of Reading (SVR).MethodA total of 342 Cantonese-speaking Chinese children in grades 3–5 were recruited to participate in the study. They were assessed on word reading accuracy and fluency, morphological awareness, vocabulary knowledge, and reading comprehension.ResultsThe confirmatory factor analysis results confirmed that reading fluency is a separate factor from decoding, linguistic comprehension, and reading comprehension. Furthermore, the structural equation modeling results revealed that reading fluency is a significant predictor of reading comprehension and a mediator between decoding and reading comprehension in the extended SVR model.ConclusionThe findings extended previous research in alphabetic languages and supported reading fluency as the bridge between decoding and reading comprehension. The present study highlighted the importance of reading fluency in Chinese reading acquisition in a theoretical framework.